Targeting JNK-1 with Small Interfering RNA: Induction of Apoptotic Pathways in PC-3 Prostate Cancer Cells - Parra, Eduardo; Rojas, Víctor; Hecht, Pedro (Research Perspectives of Microbiology and Biotechnology Vol. 9, 2025)
Jun-N-terminal kinase-1 (JNK-1) has been implicated in the transformation of primary fibroblasts and the regulation of tumor cell growth. Emerging evidence suggests that JNK-1 functions as a growth-promoting factor in prostate cancer cells, making it a potential therapeutic target. In this study, we utilized small interfering RNA (siRNA) to selectively suppress JNK-1 expression in the prostate cancer cell line PC-3. The targeted siRNA effectively reduced JNK-1 levels, leading to alterations in the expression of key apoptotic and cell cycle regulatory proteins, including p21, XIAP, and Bcl-2, while VEGF expression remained unaffected. In contrast, a control scramble siRNA did not impact the expression of these proteins. The silencing of JNK-1 was confirmed at the mRNA and protein levels via RT-PCR and western blot analysis. Functional assays revealed significant inhibition of cell proliferation, with apoptosis induction validated through flow cytometry, DNA fragmentation, and caspase activity assays. Notably, siRNA-mediated downregulation of JNK-1 led to a cell death rate of 52%, an apoptotic rate of 26%, and a viability rate of 22% after five days of treatment. These findings highlight the potential of JNK-1-targeting siRNA as a novel therapeutic strategy for prostate cancer. Further research is warranted to explore its clinical applicability.